2016
DOI: 10.3402/jev.v5.31655
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of EV isolation procedures for miRNAs detection in serum samples

Abstract: Extracellular vesicles (EVs) are emerging as potent non-invasive biomarkers. However, current methodologies are time consuming and difficult to translate to clinical practice. To analyse EV-encapsulated circulating miRNA, we searched for a quick, easy and economic method to enrich frozen human serum samples for EV. We compared the efficiency of several protocols and commercial kits to isolate EVs. Different methods based on precipitation, columns or filter systems were tested and compared with ultracentrifugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 27 publications
7
115
0
Order By: Relevance
“…In line with this, we report precipitation-based isolation to yield samples with lower purity and significant protein contamination, but excellent potential for transcriptomics-driven biomarker discovery. We agree with previous publications stating that enriching serum EVs by precipitation might be a viable strategy for biomarker discovery studies [21,23]. Alvarez et al presented similar findings for profiling RNA biomarkers in urinary EVs [9].…”
Section: Discussionsupporting
confidence: 92%
“…In line with this, we report precipitation-based isolation to yield samples with lower purity and significant protein contamination, but excellent potential for transcriptomics-driven biomarker discovery. We agree with previous publications stating that enriching serum EVs by precipitation might be a viable strategy for biomarker discovery studies [21,23]. Alvarez et al presented similar findings for profiling RNA biomarkers in urinary EVs [9].…”
Section: Discussionsupporting
confidence: 92%
“…This impact on exosome recovery in UC is congruent with the lower total number of particles seen in our UC samples compared to the kits, a trend which has also been previously observed by another group [38]. The more particles from the commercial reagents might be because PEG (polyethylene glycol)-based volume exclusion is used to precipitate non-exosome nanoparticles, such as serum protein aggregates, as supported by the lower exosome purity reported in a recent method-development study of ExtraPEG [41, 62]. …”
Section: Discussionsupporting
confidence: 89%
“…The RNA sequencing analysis revealed that miRNAs were enriched in UEVs . However, the EVs RNA patterns showed differ significantly in respect to the method used for RNA extraction . Thus, the RNA quantity and RNA distribution were measured in our study.…”
Section: Discussionmentioning
confidence: 86%